Faktor-Faktor Yang Mempengaruhi Moral Disengagement Remaja - Aprilia, Zukhrufi; Solicha, Solicha (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2013)
This research was conducted in order to know factors influencing moral disengangementamong adolescents. This research used quantitative approach with multiple regressionanalysis as tool of study. Number of samples was 270 students of SMAN 6 Jakarta with nonprobabilitysampling as technique. In this research tools of data collecting (Mechanisms ofMoral Disengangement Scale, The Measures of Life Attitudes Scale, Self-importance of MoralIdentity Scale, Interpersonal Reactivity Index (IRI) and The Multidimensional MultiattributionCausality Scale (MMCS) was modified. The research showed that sex, traitcynism, moral identity, emphaty and locus of control had significant influence toward moraldisengangement. Test of minor hypothesis was conducted and it showed that of fourindividual characteristic only locus of control influenced toward moral disengangementparticularly chance and context dimensions of external locus of control and effort dimension ofinternal locus of control, whereas trait cynism, internalization, emphatic concern scale,perspective taking and internal locus of control (ability) had no impact on moraldisengangement. The research also showed that male students have higher moraldisengangement than female students.